Modifiable risk factors for oral cavity cancer in non-smokers: A systematic review and meta-analysis. (February 2023) - Heller, Margaret A.; Nyirjesy, Sarah C.; Balsiger, Robert; Talbot, Nicholas; VanKoevering, Kyle K.; Haring, Catherine T.; Old, Matthew O.; Kang, Stephen Y.; Seim, Nolan B.
Highlights: Incidence of oral cavity cancer in non-smokers is increasing while risk factors for disease development in this population is poorly understood. We performed a systematic review and meta-analysis of the existing literature. Chewing products and various dietary, dental, and medical factors increased the risk of oral cavity cancer in non-smokers whereas alcohol was not an independent risk factor. Further research on these non-traditional risk factors is warranted to guide clinicians in primary prevention strategies. Abstract: Background: Oral cavity cancer (OCC) is traditionally associated with smoking, but there is an increasing prevalence of the disease among non-smokers. This review investigates possible modifiable risk factors in the development of OCC in non-smokers (OCCNS). Methods: PubMed, EMBASE, Web of Science, and Scopus were searched for publications prior to June 2021. Comparative studies investigating modifiable OCCNS risk factors were identified following PRISMA guidelines. Publication date, population size, and results were indexed. Study quality was assessed using MINORS (Methodological Index for Non-Randomized Studies). Factors examined by multiple studies were analyzed using random-effect meta-analysis framework. Results: Literature search resulted in 1, 625 unique publications. 52 records met inclusion criterion, investigating alcohol (n = 22), chewing products (n = 18), diet (n = 7), dental health (n = 11), and medical comorbidities (n = 6). Conclusion: This review demonstrates the paucity of large studies investigating OCCNS risk factors. Further investigation is warranted to help clinicians risk-stratify patients without traditional risk factors.